Benchmarking Container Port Technical Efficiency in Latin America and the Caribbean : A Stochastic Frontier Analysis - Morales Sarriera, Javier; Araya, Gonzalo; Serebrisky, Tomas; Briceño-Garmendía, Cecilia; Schwartz, Jordan (World Bank, Washington, DC, 2014)
This paper presents a technical efficiency analysis of container ports in Latin America and the Caribbean using an input-oriented stochastic frontier model. A 10-year panel is employed with data on container throughput, port terminal area, length of berths, and number of cranes available in 67 ports. The model has three innovations with respect to the available literature: (i) it treats ship-to-shore gantry cranes and mobile cranes separately, in order to account for the higher productivity of the former; (ii) a binary variable is introduced for ports using ships' cranes, treated as an additional source of port productivity; and (iii) a binary variable is used for ports operating as transshipment hubs. The associated parameters are highly significant in the production function. The results show an improvement in the average technical efficiency of ports in the Latin America and the Caribbean region from 36 percent to 50 percent between 1999 and 2009; the best-performing port in 2009 achieved a technical efficiency of 94 percent with respect to the frontier. The paper also studies possible determinants of port technical efficiency, such as ownership, corruption, terminal purpose, income per capita, and location. The results reveal positive, but weak, associations between technical efficiency with landlord ports and with lower corruption levels; stronger results are observed between technical efficiency with specialized container terminals and with average income.